Implementation of Monitoring System for Air Quality using Raspberry PI: Experimental Study - Abdulrahman Abdullah Alkandari; Samer Moein (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Because of rising dependency on fossil fuels, and rising amounts of toxic gases in the environment, it found that people are in need of a way to ensure the safety specifically those that live in cities. An approach is suggested in this paper, that is economical yet affords good detection, and can give accurate readings that can be analyzed and manipulated, and can even provide warnings through sending emails. These requirements are found in the Raspberry Pi when it hooked up to the sensors. This paper was focused on few dangerous gases such as Carbon Monoxide (CO), Nitrogen Dioxide (NO2) and other gases. The results in this paper showed that some gases, specifically CO, may be a problem in Kuwait as it is always slightly below the warning level. The success with the Raspberry Pi and the results were encouraging to open the way for much improvement in the future.